Zero waste through blended learning based learning for social studies education students in Malang State University - Arifin, A. Zaenal; Ibrahim, Sarah; Medida, Veneshia Auralia; Purnomo, Agus (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
Blended learning can promote a learning-friendly environment, but in reality, that method is rarely used on a massive scale because of constraints means or the ability of the individual. Therefore the focus of the study in this article is how zero waste through learning opportunities based PIPS blended learning for students at the State University of Malang. A qualitative approach with the descriptive design is used to discuss the topic of blended learning opportunities in promoting zero waste. Data collection techniques at IPS students using questionnaires and interviews to triangulate data. The implications of the findings of this research can be a support to the study of the development of blended learning opportunities on a broader scale in promoting a friendly learning environment.